Optimization of Ni loading amount in Ni-CeZrO2 catalyst for dodecane steam reforming for the upcycling of plastic pyrolysis oil - Min-Gyeong Bae; Yeol-Lim Lee; Hak-Min Kim; Ji-Won Son; Beom-Su Cheon; Dae-Woon Jeong (Fuel Processing Technology)
In response to global efforts to address plastic pollution, pyrolysis of waste plastics offers a sustainable pathway for chemical recycling and clean hydrogen production. This study focuses on the steam reforming of dodecane, a key component of light oil derived from plastic pyrolysis, to produce hydrogen. Nickel-based catalysts supported on Ce0.8Zr0.2O2 (Ni-CeZrO2) with varying Ni loadings (1, 3, 5, and 10 wt%) were synthesized using a co-precipitation method and characterized by various characterization techniques. The catalytic performance was evaluated under steam reforming conditions at 750 °C. Among the prepared catalysts, 5 wt% Ni-CeZrO2 exhibited the highest hydrogen yield and dodecane conversion due to its optimal balance of Ni0 active sites, oxygen storage capacity, and strong metal-support interaction. The 10 wt% Ni-CeZrO2 catalyst showed higher initial activity but suffered rapid deactivation due to excessive carbon formation, while lower Ni loadings (1 and 3 wt%) showed insufficient active sites for effective reforming. The results indicate that 5 wt% Ni-CeZrO2 is the optimal loading amount for the steam reforming of dodecane, providing a balance between high activity and long-term stability.